A case--control study of selenium in nails and prostate cancer risk in British men. - Allen, N; Morris, J; Ngwenyama, R; Key, T (2004)
In view of the experimental evidence suggesting that the micronutrient selenium reduces prostate cancer risk, we investigated the association between the selenium level in fingernails, a measure of long-term selenium intake, and prostate cancer risk in a case-control study among 656 British men, conducted in 1989-1992. Nail clippings were taken at the time of recruitment and selenium concentration, measured using neutron activation techniques, was successfully assayed for 300 case-control pairs and varied six-fold among the controls (0.59 p.p.m.; interquartile range, 0.50-0.71 p.p.m.). Nail selenium concentration was not significantly associated with prostate cancer risk: men in the highest quartile of nail selenium had a slightly increased risk compared with men in the lowest quartile (OR 1.24, 95 CI, 0.73-2.10); for advanced prostate cancer, men in the highest quartile had a slightly reduced risk compared with men in the lowest quartile (OR 0.78, 95% CI, 0.27-2.25). These results suggest that selenium is not strongly associated with prostate cancer risk in British men.